Seroprevalence Brucellosis in Etawah Crossbreed goat in District Siliragung, Banyuwangi - Saputro, Amung Logam; Praja, Ratih Novita; Yudhana, Aditya; Mumtazi, Fauzan; Romadhona, Ma'rifatunnisa'; Anastasya, Anastasya; Farhan, Muhammad Riesta (Universitas Airlangga, 2022)
Brucellosis is a zoonotic bacterial disease that is endemic in many countries, especially developing countries such as Indonesia. Livestock centers in Indonesia have not been free from Brucellosis disease, which reaches 40% and spread almost throughout Indonesia. This study aimed to detect the presence of Brucellosis antibodies in Etawah Crossbreed at Siliragung District, Banyuwangi using the Rose Bengal Test (RBT) method. The data that will be obtained later was expected to provide benefits in reducing the possibility of Brucellosis spread and can be used as a reference for Brucellosis control programs in goats. The results showed that the RBT examination in the sample population of Etawah Crossbreed in Siliragung District which was taken showed negative results in all samples. The conclusion of this study was that Brucella abortus antibodies were not found in Etawah Crossbreed in Siliragung District, Banyuwangi.